2002
DOI: 10.1207/s15327752jpa7802_03
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Interrater Reliability for Scoring the Rorschach Comprehensive System in Eight Data Sets

Abstract: In this article, we describe interrater reliability for the Comprehensive System (CS; Exner. 1993) in 8 relatively large samples, including (a) students, (b) experienced re- searchers, (c) clinicians, (d) clinicians and then researchers, (e) a composite clinical sample (i.e., a to d), and 3 samples in which randomly generated erroneous scores were substituted for (f) 10%, (g) 20%, or (h) 30% of the original responses. Across samples, 133 to 143 statistically stable CS scores had excellent reliability, with med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
118
4
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(143 citation statements)
references
References 65 publications
12
118
4
6
Order By: Relevance
“…Lastly, some of our inter-rater reliability values were relatively low, compared to other data reported in the literature (e.g., Meyer et al, 2002;Viglione, Blume-Marcovici, Miller, Giromini, & Meyer, 2012;Viglione & Taylor, 2003). Though both the original and re-scored records were coded by (graduate) students, the initial coding was also carefully supervised by a senior clinician and researcher who has been using the Rorschach for years.…”
Section: Limitations and Final Considerationsmentioning
confidence: 75%
“…Lastly, some of our inter-rater reliability values were relatively low, compared to other data reported in the literature (e.g., Meyer et al, 2002;Viglione, Blume-Marcovici, Miller, Giromini, & Meyer, 2012;Viglione & Taylor, 2003). Though both the original and re-scored records were coded by (graduate) students, the initial coding was also carefully supervised by a senior clinician and researcher who has been using the Rorschach for years.…”
Section: Limitations and Final Considerationsmentioning
confidence: 75%
“…A great deal of research with various Rorschach systems and scores has demonstrated strong inter-rater reliability (Acklin, McDowell, Verschell, & Chan, 2000;McDowell & Acklin, 1996;Exner, 1993;Meyer & Archer, 2001;Viglione, 1999;Viglione & Meyer, 2008;Viglione & Taylor, 2003). Inter-rater reliability for the CS (Exner, 2003) has been particularly wellestablished, with a large-scale meta-analysis of CS inter-rater reliability reporting high inter-rater reliability for the majority of CS scores (specifically, median intraclass correlations for statistically stable scores ranged from .72-.96; Meyer et al, 2002). 1 This range of reliabilities has been considered "good to excellent" by some authors (Cicchetti, 1994;Shrout & Fliess, 1979) and "acceptable to excellent" by others (Hunsley & Mash, 2008).…”
Section: Inter-rater Reliability R-pasmentioning
confidence: 99%
“…Interrater reliability, assessed by the intraclass correlation coefficient (ICC), of coder A with coder C was greater than .70 for all three motives and can thus be considered good to excellent (cf. Meyer et al, 2002; Table 1 reports detailed ICC summary information). We also determined the participants' levels of activity inhibition in the U.S. sample by counting the frequency of the word not (cf.…”
Section: Personality Measuresmentioning
confidence: 99%